Searching beyond the lamppost: Let’s focus on economically relevant questions - Oechssler, Joerg (Journal of economic behavior & organization, 2010)
Experimental economics is in danger of behaving like the famous drunk who searches for his keys under the light even though he lost them in some dark corner. It is argued that we are wasting our time (and endangering the respect that other economists have for experimentalists) by playing too much with some of our favorite toys, like the dictator game, rather than focus on new and economically relevant designs.